The Evolution of Trends and Threats in Food Consumption in the Light of Sustainable Development Goals - Wiśniewska, Małgorzata Z. (Krakow Review of Economics and Management/Zeszyty Naukowe Uniwersytetu Ekonomicznego w Krakowie, 2022)
Objective: To identify the main hazards and threats related to food consumption in the context of Sustainable Development Goals (SDGs). Research Design & Methods: The study uses secondary data analysis, including of official reports and statistics, critical analysis of the literature, comparative analysis, synthesis and logical reasoning. Findings: Important trends include mindful and conscious consumption, eco-consumption, food sharing, frugality, freeganism, personalised and hedonistic consumption, and climatarianism. The main hazards/threats discovered include difficulties population face in feeding themselves, the growing number of immunocompromised people, climate change, the emergence of the COVID-19 pandemic and other pathologies in the food market, the presence of allergens and the lack of a food safety culture. Implications / Recommendations: Analysis of the postulates contained in the SDGs makes it possible to confirm their convergence with the need to ensure food and food safety. Threats in this area often give rise to trends. In the light of the challenges of SDGs as well as pandemic and post-pandemic effects, hedonistic needs and trends are important: They are connected with ensuring health and greater care for one’s own mental and physical condition. The situation in Ukraine is certainly suggests the need to develop shared and collaborative consumption. Contribution: The paper reviews and systematises trends, threats and hazards in food consumption from the perspective of individual sustainable development goals. This is the first publication of this type in Poland.